Analisis Dan Perancangan Sistem Informasi Unit Kegiatan Mahasiswa (UKM) Berbasis Web Pada Universitas Dharma Andalas - Eko Mardiyansyah; Sularno Sularno; Faradika Faradika; Zulfahmi Zulfahmi (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
In carrying out the process of registering new members, disseminating information and managing data on the management of the Student Activity Unit (UKM) of Dharma Andalas University, Padang. And that is a problem for UKM administrators on the campus. An information system is needed that can manage the data collection process for registrants, dissemination of information on SME activities, as well as manage data files - data reports from SME management in a more structured manner.The purpose of this research is to design a web-based information system that can facilitate the management of UKM Dharma Andalas University activities, Padang and make it easier to register new members. There are 3 users who can access this system, namely main admin, UKM administrators and students. Each of them has a different role. The student page contains some information such as UKM profiles, announcements, registration, activity information and news about UKM. The method used in this research is the prototype method and the PHP programming language, MySQL as the database. The results of this study are to make it easier for UKM Dharma Andalas University to carry out the process of registering new members for UKM Dharma Andalas University and also to manage file management for each UKM easier and faster.